EFFECTIVE METHODS AND WAYS OF TEACHING ENGLISH IN PRIMARY SCHOOL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
As the world becomes ever more connected, the appeal of learning a new language is clear.